Appendage Development in Clostridium bifermentans - Samsonoff, William A. (1971)
The appendages of Clostridium bifermentans UK-A 1003 spores were shown to originate from a substance located just exterior to the outer forespore membrane. The dense spore coat develops along the periphery of this material, and, as the appendages develop in the cytoplasm, the coalescing spore coat intervenes between the appendages and their origin. Freeze etching revealed that the appendages are in the form of distinct fibers in proximity to the mature spore body. These fibers form a network around the spore, seemingly encasing it and insuring that the appendages remain attached to the mature, free spore. The inner wall of each appendage tubule is lined with fibers whereas the outer surface is smooth. The developing exosporium contained several layers consisting of small (3 nm) globular subunits; the outer exosporial surface is composed of relatively unstructured material.